Happiness Research: A Review of Critiques - Ashley Frawley (Sociology Compass, 2015)
This article examines critiques raised in response to the growing interest in 'happiness' across a range of academic disciplines. It presents three major areas of contention including the culture-bound and normative character of happiness, happiness research's reliance upon 'bad science' and scientism, and its tendency to promote a 'diminished subjectivity' and to individualise social problems. It argues that critique may represent the maturation of the field, but that the depth of some critiques points to the possibility that the explanatory power of happiness has reached its breaking point and is likely to be superseded.